Sodium formate induces development-dependent intestinal epithelial injury via necroptosis and apoptosis - Jingjing Wei; Yuan Tian; Meiqi Guan; Jinshu Wei; Yong Ji; Guozhong Tao; Karl G. Sylvester (Redox Report)
Objectives Necrotizing enterocolitis (NEC) is a common and sometimes fatal disease affecting premature infants. Elevated formate has been found in the stool of patients with NEC. Sodium formate (NaF) is used to explore the role of formate in the intestinal epithelial injury.Methods In this study, 150 mM NaF solution was intraluminally injected in 14-day-old and 28-day-old mice. Mice were sacrificed after 24 h of feces collection, and the blood and small intestinal tissues were collected to detect the pathological damage of intestinal tissue, intestinal permeability, oxidative stress indicators including SOD, HO-1, MDA, and 4-HNE, inflammatory cytokines including IL-1β, TNF-α and IL-6, mitochondrial function such as ATP and PGC-1α in mice intestinal tissue, indicators of the cell death modes including necroptosis-related protein RIPK1 and p-MLKL, and apoptosis- related protein cleaved-caspase-3 and p-AKT (S473).Results NaF treatment significantly damaged intestinal epithelial tissue and barrier function, caused mitochondrial dysfunction, manifesting as decreased ATP and PGC-1α levels, increased lipid peroxidation products MDA and 4-HNE, depleted antioxidant enzyme SOD, and upregulated the expression of HO-1. Furthermore, NaF treatment induced inflammatory responses by promoting the release of IL-1β, IL-6 and TNF-α in a development-dependent manner, eventually inducing necroptosis and apoptosis.Conclusions Formate may be a source of metabolic intestinal injury contributing to the pathogenesis of NEC in human newborns.